(untitled) (Cadernos de Sociomuseologia, 2010)
The present document intends to analyze the different ecomuseums visited and studied in Japan trying to describe the reality of Japanese ecomuseology. From the descriptions of Japanese ecomuseums extrapolate the main features to build a model that is a possible reference for the XXI century ecomuseums.